2015
DOI: 10.1002/aenm.201500386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkyl Terminal Chains on Morphology, Charge Generation, Transport, and Recombination Mechanisms in Solution‐Processed Small Molecule Bulk Heterojunction Solar Cells

Abstract: Length of the terminal alkyl chains at dicyanovinyl (DCV) groups of two dithienosilole (DTS) containing small molecules (DTS(Oct)2‐(2T‐DCV‐Me)2 and DTS(Oct)2‐(2T‐DCV‐Hex)2 ) is investigated to evaluate how this affects the molecular solubility and blend morphology as well as their performance in bulk heterojunction organic solar cells (OSCs). While the DTS(Oct)2‐(2T‐DCV‐Me)2 (a solubility of 5 mg mL−1) system exhibits both high short circuit current density (J sc) and high fill factor, the DTS(Oct)2‐(2T‐DCV‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 69 publications
11
111
0
Order By: Relevance
“…20 The topographic AFM images of the blended films determined for the optimized OSCs are given in Fig. 9.…”
Section: Film Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…20 The topographic AFM images of the blended films determined for the optimized OSCs are given in Fig. 9.…”
Section: Film Morphologymentioning
confidence: 99%
“…The replacement of the active hydrogen by an alkyl group was found to be an efficient tool not only to increase the electrochemical stability of donor-acceptor small molecules, 15,16 but also to control their solubility and a number of important solid-state physical properties by simple adjustment of the alkyl chain length in the DCV substituent. 17,18 To fine-tune the energy levels in small molecules, some additional electron-donating blocks such as dithienosilole, [19][20][21][22] benzodithiophene, 23,24 and dithienopyrrole, 25 and etc., are often used. For the design of star-shaped molecules, a triphenylamine (TPA) core is one of the widely used electron-donating blocks due to its low cost, high electrochemical stability and hole transporting ability.…”
Section: Introductionmentioning
confidence: 99%
“…Besides bulk recombination, 1,4,17,18 surface recombination is a further limiting loss mechanism for high performance OPV devices and was recently proven to be much more relevant than originally suggested. 19 Suitable interface layers are necessary to enable the loss-free extraction of the respective carriers at a rate higher than the bimolecular recombination rate.…”
Section: 3mentioning
confidence: 99%
“…S28b †) is complex and not fully understood, although multiple studies reported that the solution evaporation rate does impact the crystallization kinetics of dominantly the donor phase. 18,35 It illustrates that a reasonable explanation of the device characteristics should consider simultaneously both the molecular solubility and morphology. Since these DTS-based oligomers show a similar HOMO energy level (see Table 2), the V oc values for all of the devices are closely distributed around 0.90 V, with DTS(Oct) 2 -(2T-DCV) 2 being the only exception.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation